Gambaran Permasalahan Pasangan Muda di Kabupaten Kerinci - Rezki Hariko; Opi Andriani; Taufik Taufik (JKI (Jurnal Konseling Indonesia), 2022)
Young married couples are faced with various problems, as a consequence of not reaching psychological, physical, social, economic and cultural maturity. This study aims to describe the problems experienced married couples at a young age. Research respondents were 46 young married couples in Kerinci. The research data was collected using instruments arranged according to the Guttman scale model. The research findings indicate a problem in each indicator, that is related to the state of self; social relations with the community; economics and finance; work, religion, values and norms; circumstances in the family; and sexual intercourse. Based on the research findings, it is suggested to counselor to do counseling and guidance service to young married couples who will and have been married to prevent and alleviate the problem in an effort to realize happy family.